2012
DOI: 10.1136/annrheumdis-2011-143578
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the efficacy of the P2X7purinergic receptor antagonist AZD9056 on the signs and symptoms of rheumatoid arthritis in patients with active disease despite treatment with methotrexate or sulphasalazine

Abstract: ClinicalTrials.gov NCT00520572.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
172
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(177 citation statements)
references
References 9 publications
(7 reference statements)
4
172
0
1
Order By: Relevance
“…P2X3, P2X2/3, P2X4, and P2X7 receptors have received a lot of recent attention as potential targets to treat a variety of conditions that include chronic pain and arthritis [44]. Clinically the P2X7 receptor antagonists CE-224535 and AZD9056 have not demonstrated efficacy in rheumatoid arthritis and it is unknown whether they may be useful in pain indications [45,46]. P2X3 receptor expression changes in animal pain models of P2X3 knock-out mice have shown the development of reduced mechanical allodynia [47] and neuronal P2X3 receptor activation predisposing afferent neurons to inflammatory hyperalgesia [48].…”
Section: Introductionmentioning
confidence: 99%
“…P2X3, P2X2/3, P2X4, and P2X7 receptors have received a lot of recent attention as potential targets to treat a variety of conditions that include chronic pain and arthritis [44]. Clinically the P2X7 receptor antagonists CE-224535 and AZD9056 have not demonstrated efficacy in rheumatoid arthritis and it is unknown whether they may be useful in pain indications [45,46]. P2X3 receptor expression changes in animal pain models of P2X3 knock-out mice have shown the development of reduced mechanical allodynia [47] and neuronal P2X3 receptor activation predisposing afferent neurons to inflammatory hyperalgesia [48].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that inhibition of the expression of inflammatory cytokines prevents the decomposition of cartilage tissues [15]. The characteristic features of OA include knee joint edema, decomposition of cartilage, hyperplasia of synovium and degradation of sub-chondral bones [16].…”
Section: Discussionmentioning
confidence: 99%
“…Block of P2X7 receptor signalling in the collagen-induced arthritis animal model of RA inhibited peripheral inflammatory tissue destruction and the autoreactive humoral response, supporting the view that P2X7 receptor antagonists may cure inflammatory autoimmune diseases, such as RAs [389]. However, a later study claimed that AZD9056, a P2X7 receptor antagonist, did not appear to be a therapeutically useful target for RA [390]. P2X7 receptor antagonists are also being explored for the treatment of inflammatory pain in joints [391].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%